2020
DOI: 10.1155/2020/9540810
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antihypertensive Treatment and Associated Factors in Central Ethiopia

Abstract: Background. Adherence to treatment is a primary determinant of treatment success. Nonadherence attenuates clinical benefits to the recipients of the treatment. However, monitoring adherence to long treatment regimens is not given due emphasis in low-income contexts. This study aimed to assess adherence to antihypertensive treatment and factors associated with it in Central Ethiopia. Method. This is an institution-based cross-sectional study conducted in 4 public hospitals in Central Ethiopia from December 4, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 51 publications
3
22
0
1
Order By: Relevance
“…Fourteen studies evaluated the impact of social support on medication adherence; ten cross-sectional studies and four interventional studies. 8,10,[22][23][24][25][26][27][28][29][30][31][32] The cross-sectional studies included in this study used different scales and questionnaires to measure social support as shown in Table 3, while in the interventional studies, family members, friends or pharmacists were designated as supervisors of hypertensive patients. Family members or friends educated patients about the illness and medications, reminded them Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies evaluated the impact of social support on medication adherence; ten cross-sectional studies and four interventional studies. 8,10,[22][23][24][25][26][27][28][29][30][31][32] The cross-sectional studies included in this study used different scales and questionnaires to measure social support as shown in Table 3, while in the interventional studies, family members, friends or pharmacists were designated as supervisors of hypertensive patients. Family members or friends educated patients about the illness and medications, reminded them Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…4 Moreover, inadequate treatment and poor adherence lead to long-term complications such as stroke, health failure, and chronic kidney disease, 9 , 10 and hospitalization. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, compared to research from other countries, we found the similar proportion of high medication adherence in our population. Although most studies used different tools to assess medication adherence, studies in Asian countries also reported a similar trend [11,[26][27][28][29]. For example, a study in a public primary care clinic in Singapore using the Medication Adherence Report Scale-5 (MARS-5) reported that about 55% of the participants had high medication adherence [28].…”
Section: Discussionmentioning
confidence: 96%
“…For example, a study in a public primary care clinic in Singapore using the Medication Adherence Report Scale-5 (MARS-5) reported that about 55% of the participants had high medication adherence [ 28 ]. A study in Malaysia using the seven-item validated survey form for medication adherence reported that around 53% had good adherence [ 29 ].…”
Section: Discussionmentioning
confidence: 99%